2001
DOI: 10.1079/bjn2000225
|View full text |Cite
|
Sign up to set email alerts
|

Elevated acute-phase protein in stunted Nepali children reporting low morbidity: different rural and urban profiles

Abstract: This study examined the associations between severity of stunting, plasma protein concentrations and morbidity of 104 Nepali boys, aged 10±14 years, living in contrasting environments. Boys from a remote village were compared with three similarly aged urban groups: poor squatters, homeless street children, and middle-class schoolchildren. All but the middle-class group were stunted, particularly village boys whose mean height-for-age z-score (22´97, SD 0´82) indicates severe growth retardation. Stunting was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 21 publications
(28 reference statements)
0
42
0
1
Order By: Relevance
“…Fever and persistent diarrhoeas are common early symptoms in HIV-infected children (Dobosz & Marczynska, 2004), and Filteau et al (1995) have also found diarrhoea in the previous week to be associated with several elevated acute-phase proteins in preschool Ghanaian children. Panter-Brick et al (2001) have reported that stunting is associated with high plasma ACT concentrations in Nepali village children even though morbidity appears to be low. Northrop-Clewes et al (1994) have also reported that mean plasma ACT concentrations are elevated in >50 % of apparently-healthy Gambian infants every month over 1 year.…”
Section: Measuring Subclinical Inflammation In the Apparently-healthymentioning
confidence: 99%
“…Fever and persistent diarrhoeas are common early symptoms in HIV-infected children (Dobosz & Marczynska, 2004), and Filteau et al (1995) have also found diarrhoea in the previous week to be associated with several elevated acute-phase proteins in preschool Ghanaian children. Panter-Brick et al (2001) have reported that stunting is associated with high plasma ACT concentrations in Nepali village children even though morbidity appears to be low. Northrop-Clewes et al (1994) have also reported that mean plasma ACT concentrations are elevated in >50 % of apparently-healthy Gambian infants every month over 1 year.…”
Section: Measuring Subclinical Inflammation In the Apparently-healthymentioning
confidence: 99%
“…As such, they can be measured as a nonspecific indicator of the degree of investment in antipathogen defenses. Panter-Brick et al (2000) reported a negative association between ACT concentration and height-for-age z-scores (HAZ) in Nepali children.…”
Section: Childhoodmentioning
confidence: 99%
“…To date we have reported marked group differences in the physical markers of well-being indicating that the homeless street boys did not have the worst outcomes in terms of growth status and pathogen load, and documenting a marked contrast between urban and rural conditions. Height status was worst in villagers and acute-phase protein indices of pathogen load were greatest even though villagers reported the least morbidity (Panter-Brick, Lunn, Baker, & Todd, 2001;Panter-Brick, Todd, Baker, & Worthman, 1996). Indeed, the observed discordance between self-reported symptoms and infection status raised our interest in biomarkers to assess health status.…”
Section: Selection Of Study Groupsmentioning
confidence: 99%
“…Assay detection limit is 0.02 g/l; within-and between-assay CVs for low and high controls (0.24 and 0.59 g/l) run 3 and 4%, and 5 and 8%, respectively. Procedure, performance, and quality control for the results reported here are detailed elsewhere (Adelekan et al, 2003;Panter-Brick et al, 2001). ACT rises rapidly and remains elevated in response to pathogen exposure, and thus acts as an indicator of pathogen challenge in subclinical and chronic infection (Adelekan et al, 2003;Thompson, Milford-Ward, & Whicher, 1992).…”
Section: Biomarkers and Demographic Datamentioning
confidence: 99%